Utilization of educational applications in assessing the reading skills of junior high school students - Hidayat, Didin Nuruddin; Mulyati, Yatni Fatwa; Husna, Nida (citeus, 2022)
Globalization and the advancement of technology are giving a new challenge as well as opportunities for English educators around the globe. Indirectly, there are obstacles associated with learning English due to the fact that technology has become an integral aspect of human existence. The teaching of reading skill also faces the same challenge. Nowadays, reading is seen as more important than other skills, considering that reading has become one of the aspects of literacy. With regard to assessment, the availability of an educational application might be advantageous for teachers to assess students' reading skills. The current study investigates the types of application used by teachers in assessing students’ reading skill and the type of reading assessment that occur during the implementation of the application. Through open-ended interview and document analysis method, the research result indicates that the implementation of Google Form as an educational application to assess students reading skills demonstrated a reading assessment based on traditional assessment approaches with a focus on intensive reading. This study has shown the appropriate media for assessing students reading skill along with the reading focuses and assessment design that is suitable for it. In addition, in this study, Google Form dominates the most considerable use of media to assess students reading skills. Therefore, teachers could also save more time in assessing students’ reading by utilizing educational applications.